DIAGNOSIS OF INFANTILE NEPHROTIC SYNDROME: CLINICAL AND LABORATORY EVALUATION - Seabra, Lucas dos Anjos; de Macedo, Ryan Rafael Barros; Vieira, Carolina Sena; Oliveira, Juliana Cristina Santana Lima Queiroz; de Azevedo, Gabriel Felicio; Estrela, Sillas Abrantes; Silva, Maria Isabele dos Santos; Borges, Milena Raquel de Brito Crisostomo; Gomes, Bruno da Silva; Matias, Maryah Edwarda Natan Rodrigues; Savi, Igor Alves; Cavalcante, Erica Ribeiro; et al. (Seven Editora, 2026)
Nephrotic syndrome (NS) is a common pediatric disease characterized by dysfunction in the glomerular filtration barrier leading to the loss of protein, fluid, and nutrients in the urine. Corticosteroid therapy is the conventional treatment in children. Long-term complications of NS and prolonged steroid exposure affect bones, growth, and the cardiovascular system. Diet can play an important role in preventing these complications, but there is a scarcity of scientific literature on nutritional recommendations for children with NS. They need individualized nutritional choices not only during the acute phase of the disease but also during remission to prevent the progression of kidney damage. Proper dietary management in these children requires a multidisciplinary approach involving family pediatricians, pediatric nephrologists, nutritionists, and parents. DOI: https://doi.org/10.56238/sevened2026.002-006